Effect of elevated nitrate and sulfate concentrations on selenate removal by mesophilic anaerobic granular sludge bed reactors. Issue 2 (20th December 2017) - Tan, Lea Chua; Nancharaiah, Yarlagadda V.; van Hullebusch, Eric D.; Lens, Piet N. L.
Abstract : The molar ratio of NO3 − and SO4 2− to SeO4 2− is a key factor in SeO4 2− removal. A UASB reactor showed no inhibition of SeO4 2− at high NO3 − and SO4 2− concentrations achieving 100% NO3 −, 30% SO4 2− and 80% total Se removal efficiencies. Abstract : Simultaneous removal of selenate (SeO4 2− ), nitrate (NO3 − ) and sulfate (SO4 2− ), typically present in Se-contaminated wastewaters, by Eerbeek anaerobic granular sludge, was investigated in batch and continuous bioreactor experiments. Batch experiments showed that SeO4 2− removal was enhanced to 91% in simulated wastewater with SeO4 2− + NO3 − + SO4 2− (1 : 40 : 100 SeO4 2− : NO3 − : SO4 2− molar ratios) compared to simulated wastewater with SeO4 2− alone (67%). SeO4 2− removal was severely impacted by high concentrations of SO4 2− (SeO4 2− : SO4 2− > 1 : 300). Removal of SeO4 2−, NO3 − and SO4 2− at a 1 : 40 : 100 ratio was studied in a 2 L lab-scale upflow anaerobic sludge blanket (UASB) reactor operated at 20 °C, a 24 h hydraulic retention time and a 2 g COD L −1 day −1 organic loading rate using lactate as the electron donor. The removal efficiencies were stabilized at 100, 30 and 80% for NO3 −, SO4 2− and total Se, respectively, during 92 days of UASB operation. The total Se removal efficiencies dropped to 47% or even to a negative value when, respectively, SO4 2− and NO3 − were sequentially excluded from the influent. Speciation of Se, particularly the microbial production of colloidal Se 0 levels, was influenced by both SO4 2− and NO3 − . The results presented here demonstrate that UASB reactors are capable of removing SeO4 2− in the presence of millimolar concentrations of NO3 − and SO4 2− typically found in Se-contaminated wastewaters.